Pengaruh Teknik Assertive Training dalam Konseling Kelompok Terhadap Prokrastinasi Mengerjakan Skripsi Pada Mahasiswa - Anggraini, Shavira; Farid, Dimas Ardika Miftah (Indonesian Journal of Education and Learning, 2025)
Examining the effects of group counseling's assertive training approach on students' tendency to put off writing their theses is the primary goal of this research. The approach used is a one-group pre-test-post test design, which is common in quantitative research. Data was collected using a procrastination measurement. Five students with moderate to high levels of procrastination were selected for the research sample. These students were from the 2021 Guidance and Counseling class at Adi Buana PGRI University in Surabaya. After participating in group counseling therapy that included assertive training techniques, participants' procrastination levels dropped. The results of the Asymp. Sig. (2-tailed) Wilcoxon test were 0.043, which is less than 0.05, and thus, Ha was accepted and Ho was rejected. Thus, students who use aggressive training strategies in group counseling tend not to delay working on their thesis.